2020
DOI: 10.1007/s00392-020-01773-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicentric validation of a novel prediction model for paroxysmal atrial fibrillation

Abstract: Background The early recognition of paroxysmal atrial fibrillation (pAF) is a major clinical challenge for preventing thromboembolic events. In this prospective and multicentric study we evaluated prediction scores for the presence of pAF, calculated from non-invasive medical history and echocardiographic parameters, in patients with unknown AF status. Methods The 12-parameter score with parameters age, LA diameter, aortic root diameter, LV,ESD, TDI Aʹ, heart frequency, sleep apnea, hyperlipidemia, type II di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previously, the end‐systolic diameter and end‐diastolic diameter of the left ventricle as well as left atrial diameter were identified as strong predictors of AF. 50 In the future, analyzing transcriptional modules associated with these miRNAs could reveal pathways associated with the molecular pathology of AF. Known associations of miRNAs with AF could be confirmed (miR‐21, miR‐29b, and miR‐34a) and new associations with AF were identified (miR‐9, miR‐23a, miR‐485).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the end‐systolic diameter and end‐diastolic diameter of the left ventricle as well as left atrial diameter were identified as strong predictors of AF. 50 In the future, analyzing transcriptional modules associated with these miRNAs could reveal pathways associated with the molecular pathology of AF. Known associations of miRNAs with AF could be confirmed (miR‐21, miR‐29b, and miR‐34a) and new associations with AF were identified (miR‐9, miR‐23a, miR‐485).…”
Section: Discussionmentioning
confidence: 99%
“…While validated in Hispanic patients at large, disaggregation is not reported, making it difficult to know if this tool is appropriate to use in all Hispanic subgroups. More novel risk tools, such as the ECHO-AF score [ 65 ], do not report the ethnic breakdown of their study cohorts, preventing validated use in Hispanic populations. Among the well-established risk factors for AF incorporated into these risk algorithms are age, HTN, DM, obesity, myocardial infarction, coronary artery disease, and HF.…”
Section: Risk Assessment In Hispanic Individuals In the Usamentioning
confidence: 99%
“…in the prediction of stroke and bleeding risks 143 , 144 and are typically derived from large-scale registries and trials that investigated the relevant clinical outcomes. Statistical models have also been applied to several of the current challenges in AF management, including early AF detection, 90 , 91 rhythm-control management, 100 and AF recurrence prediction. 101 Several statistical models have combined conventional risk scores based on clinical characteristics with biomarkers to increase their predictive performance.…”
Section: Data-driven Models For Af Managementmentioning
confidence: 99%